Potential challenges in a witness protection programme in Malaysia - Sandhu, Sarvinder Kaur (Universiti Putra Malaysia Press, 2011)
Witness protection is a programme which protects crucial witnesses whose testimony may put them or their family members in jeopardy. Many countries including Malaysia have included the witness protection programme into the federal legislation. The United States, which has implemented witness protection programme since the 1970s, has reported a high rate of convictions as compared to countries without such a programme. Malaysia has recently passed the Witness Protection Act and therefore it is relatively new in matters pertaining to witness protection programmes. Lessons can be learnt from countries which have long implemented such programmes. Common issues which Malaysia may face include matters such as finances and resources, the ambiguity of certain terms in the legislation and problems when witnesses are relocated or change of identity. Other problems include the maintaining of participants in the programme and the termination of it. There is also the issue of whether the programme is rebirthing and rewarding criminals. This happens when the participant is a criminal herself/himself, i.e. whose punishment is reduced or relocated to another neighbourhood in lieu of her/his testimony to convict a 'bigger' criminal. These participants sometimes continue their 'criminal' activities in the new community they are relocated to, and thus, pose a risk to the residents in the new community. It is undeniable that problems will exist and with experience, they can be ironed out periodically. This article briefly views these problems.